2003
DOI: 10.1046/j.1439-0442.2003.00518.x
|View full text |Cite
|
Sign up to set email alerts
|

Xylazine does not Induce Retrograde Flow of Spermatozoa into the Urinary Bladder of Sexually Rested Boars

Abstract: The effect of xylazine on the retrograde flow of spermatozoa from their storage sites in the epididymides and vasa deferentia into the urinary bladder of sexually rested boars was examined. The bladder of four boars was evacuated through a surgically implanted urinary catheter and the urine was examined for the presence of spermatozoa. Boars were then given an injection of 2.2 mg of xylazine per kilogram of body weight and, immediately thereafter, 500 ml of saline was infused into the urinary bladder. Approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Sperm were found in all dog urine samples after ejaculation, despite the fact that the pretreatment with sympathomimetic agents significantly decreased the retrograde flow [ 31 ]. In contrast, no significant differences in the percentage of the retrograde flow of sperm were observed after the administration of xylazine in pigs [ 32 ] or medetomidine in cats [ 22 ]. The same authors also assert that a small amount of sperm can be found in the urine of cats after electroejaculation even without the use of a chemical restraint or an ejaculation stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Sperm were found in all dog urine samples after ejaculation, despite the fact that the pretreatment with sympathomimetic agents significantly decreased the retrograde flow [ 31 ]. In contrast, no significant differences in the percentage of the retrograde flow of sperm were observed after the administration of xylazine in pigs [ 32 ] or medetomidine in cats [ 22 ]. The same authors also assert that a small amount of sperm can be found in the urine of cats after electroejaculation even without the use of a chemical restraint or an ejaculation stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Another common problem observed during EEJ procedures is urine-contaminated semen. In order to avoid this, α-2 adrenergic action of xylazine combined with ketamine is used to induce bladder neck closure (Martin et al, 2003).…”
Section: Introductionmentioning
confidence: 99%